PERSEPSI MASYARAKAT TERHADAP LAYANAN DOMPET DIGITAL - Jasmine Rahmawati (2022)
Improving technology when using electronic money payment systems, currently there is the development of new services in the form of digital wallets or electronic wallets. Digital wallet or e-wallet is one of the fintech products that is now well known to the public. People's perceptions of digital wallets vary. Because the use of digital wallets is diverse and people are basically diverse, different perceptions arise regarding transaction services through digital wallets. This writing aims to find out how people perceive the use of digital wallets. These perceptions are about speed, safety and comfort. The results of this paper indicate that most people feel very fast in transacting through digital wallets, which means they have a good level of speed in the transaction process. So that it makes people like to transact using digital wallets because it can save their time, people also feel very safe in transacting through digital wallets which means it has excellent security features and people feel very comfortable in transacting through digital wallets which means it has excellent service features. So that it makes people comfortable and will always transact using a digital wallet.